2007
DOI: 10.1637/7590-040206r1.1
|View full text |Cite
|
Sign up to set email alerts
|

H9N2 Influenza Viruses from Israeli Poultry: A Five-Year Outbreak

Abstract: Since 2000, hundreds of H9N2 viruses have been isolated from all types of domestic birds. Although H9N2 is a low-pathogenicity virus, disease has been observed in all types of poultry in the field. Clinical signs ranged from very mild disease to high morbidity and mortality when the virus was associated with a secondary pathogen. Because of the wide range of the virus and the great losses it caused, initially a local vaccination program was implemented, but mass vaccination was quickly authorized. A local stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 13 publications
3
47
0
Order By: Relevance
“…The H9N2 subtype of AIV was spreading in many European, Asian, African, and American countries [1,2,[4][5][6][7][8][9][10][11][12][13][14]. Highly pathogenic H5N1 virus caused major outbreaks among poultry in European, Asian, and African countries [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The H9N2 subtype of AIV was spreading in many European, Asian, African, and American countries [1,2,[4][5][6][7][8][9][10][11][12][13][14]. Highly pathogenic H5N1 virus caused major outbreaks among poultry in European, Asian, and African countries [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In reviews of Alexander [1], Senne [2], Brown et al [11], and Banks et al [14] were described general aspects of epidemiology and ecology of the AIV. Molecular and biologic characteristics of H9N2 viruses were presented by Monne et al[4], Jackwood et al [5], Banet-Noach et al [6], Aamir et al [7], Torogi et al [8], Perk et al [9,10], Nili et al [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evolutionary genetic analysis has indicated that East Asia has been the major source of H9N2 in the Middle East area [17]. Circulation of H9N2 viruses in the Middle East and Northern Africa since the year 2000 has been frequently reported in Israel, Jordan, Lebanon, Saudi Arabia, the United Arab Emirates, Kuwait, Iraq and Libya, where inactivated vaccines have been implemented in some countries to combat H9N2-associated disease of economical importance in poultry [5,8,17,36]. Nevertheless, isolation of H9N2 virus from poultry has not yet been reported from Egypt, whereas the endemic status of H5N1 virus in poultry in Egypt with frequent, and occasionally fatal, transmissions to the human population since 2006 is well known [3].…”
mentioning
confidence: 99%
“…H9N2 viruses of each of the three sublineages, G1, Y280, and Korean, were recently isolated from wildbirds and poultry worldwide [3,6,27]. H9N2 viruses were also isolated from pigs and humans in China [4,5,37] and Korea, suggesting that these viruses have the potential to cause pandemic influenza in humans.…”
Section: Discussionmentioning
confidence: 99%